Grandparents in the classroom. (Journal of Parents and Teachers, 2014)
Since grandparents are also responsible in the education of children, it is a good idea to invite them to the classroom so that everyone gets rich. This article offers ideas for inviting grandparents to class and doing various activities with and for them.
Keywords: Grandparents; education; learning community; activities.